2019
DOI: 10.1038/s41419-019-1576-3
|View full text |Cite
|
Sign up to set email alerts
|

The expression and function of TRPV4 channels in primate retinal ganglion cells and bipolar cells

Abstract: The transient receptor potential vanilloid 4 (TRPV4) channel may be opened by mechanical stimuli to mediate Ca 2+ and Na + influxes, and it has been suggested to mediate glaucoma retinopathy. However, it has been mostly unclear how TRPV4 activities affect the function of primate retinal ganglion cells (RGCs). We studied RGCs and bipolar cells (BCs) in the peripheral retina of the old-world primate using whole-cell current-clamp and voltage-clamp recordings, immunom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 59 publications
6
55
0
Order By: Relevance
“…[39][40][41][42]57,58 TRPV4 colocalizes with AQP4 in the end feet of Müller glial cells. 39 Activation of TRPV4 in swollen Müller cells has been reported to contribute significantly to the development of different retinal diseases, such as retinal detachment, 41 glaucomatous retinopathy, 40,57 and photoreceptor death. 41 In this study, although 4-HNE treatment did not alter TRPV4 expression in Müller cells, it significantly disrupted the distribution of actin filaments and altered TRPV4 localization patterns.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42]57,58 TRPV4 colocalizes with AQP4 in the end feet of Müller glial cells. 39 Activation of TRPV4 in swollen Müller cells has been reported to contribute significantly to the development of different retinal diseases, such as retinal detachment, 41 glaucomatous retinopathy, 40,57 and photoreceptor death. 41 In this study, although 4-HNE treatment did not alter TRPV4 expression in Müller cells, it significantly disrupted the distribution of actin filaments and altered TRPV4 localization patterns.…”
Section: Discussionmentioning
confidence: 99%
“…26,44,45 Previous studies have shown that TRPV4 channel activation enhances the mEPSC frequency and membrane excitability. 15,19 Surprisingly, TRPV4 channel activation in our study enhanced the inhibitory inputs of RGCs, which may have led to reduced RGC excitability (Figure 3). Because inhibitory inputs in the retina are mediated by GlyRs and GABA A Rs, we examined the effects of TRPV4 channels on these two receptors; our results showed that activation of TRPV4 channels enhanced GlyR-and reduced GABA A Rmediated inputs, suggesting that GlyRs played a major role in modulation of TRPV4 channel-mediated inhibitory inputs under our experimental conditions (Figures 6 and 7).…”
Section: Activation Of Trpv4 Channels Modulates Glyr-and Gabar-medimentioning
confidence: 68%
“…15,[59][60][61] In glaucoma, optic disc cupping may stretch RGC axons. 62,63 Therefore, mechanosensitive channels (including TRPV4 channels) might be activated by pathological elevated intraocular pressure 19,64 ; this effect could modulate GlyR-mediated inhibitory inputs. Our study showed that GlyR function and expression were enhanced by TRPV4 channel activation, emphasizing the importance of GlyRs in cell protection 65,66 ; thus, GlyRs may be effective targets for TRPV4 channel-induced modulation of RGC survival in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of various TRP channels in the retina and their importance in vision pathophysiology and other retinal functions have been reported [37][38][39][40] . Studies on the role of TRPV1 in models of retinal damage have led to conflicting results, probably due to the different types of applied insult.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas TRPV1 activation in retinal explants has been reported to promote cell death, and its inhibition to protect retinal ganglion cells from a hydrostatic pressure insult 41,42 , pharmacological inhibition or genetic deletion of this channel has also been reported to exacerbate the IOP-related damage after 5 weeks 43 . TRPV4 expression has also been associated with increased excitability in isolated retinal ganglion cells and retinal explants in response to membrane stretch, resulting in intracellular calcium mobilization and cell death 37 . However, neither Trpv1 −/− nor Trpv4 −/− mice were protected against these ill effects.…”
Section: Discussionmentioning
confidence: 99%